Synthesis and Characterization of Biodegradable HemostatGelatin Sponge forSurgery Application: Biodegradable hemostat gelatin sponge - Rana Imani,; Shahriar Hojjati Emami,; Maryam Kabiri,; Mohsen Rabbani,; Mohammad Rafienia, (Iranian Journal of Pharmaceutical Sciences, 2008)
Production and characterization of soft cross-linked gelatin sponge by using glutaraldehyde for blood hemostasis application, is the goal of this study.Biodegradable hydrogels were prepared through crosslinking of gelatin with glutaraldehyde followed by freeze drying. The effects of gelatin concentration, amount of crosslink agent and freeze drying temperature on mechanical properties andelasticity, stability and degradation rate, swelling and water absorption ability,hemostatic effect and cytotoxicity were investigated. As the freezing temperature was lowered, the density of freeze-dried sponges increased. Density of samples is strongly dependent on the freezing temperature before freeze-drying. The addition of GTAas cross linker agent changed density very slightly, but no direct relationship between the amount of cross linker and the density was observed. Gelatin sponges prepared by freeze-drying after freezing at -10 and -25 ºC had large pores. Network structure of heterogeneous pores. The rate of weight loss decreased with increasing degree of crosslinking of the samples, and the higher degree of cross-linking in gelatin sponges causes more resistance to degradation in PBS solution. Gelatin concentration increase had very sharp effect on raising the compression module, and freezing temperature changed inner structure of sponges and can affect mechanical behavior.